Tarekat Haddadiyah di Nusantara Abad Ke-17: Transmisi Intelektual, Jaringan Spiritualitas, dan Dinamika Lokalitas dalam Perspektif Tasawuf - Yasirul Musyaffa Yasir; M Syukron Jazilah; Gina Husniati Zahra; Ayatulloh (Ma'had Aly Idrisiyyah, 2026)
This article investigates the evolution of the Haddadiyah Sufi order in 20th-century Indonesia by examining its intellectual transmission, spiritual networks, and local adaptations. Rooted in the teachings of Imam al-Habib Abdullah bin Alawi al-Haddad of Hadramaut, the Haddadiyah order represents a form of amali (practical) Sufism that harmonizes ritual practices, spiritual ethics, and inclusive religious engagement. Employing a qualitative approach based on textual analysis and historical interpretation, this study reveals how the Haddadiyah tradition was disseminated through non-formal religious circles and the dynamic roles of Ba‘Alawi scholars. The findings highlight the order’s success in embedding its spiritual practices into local cultures while maintaining theological authenticity. Furthermore, the use of digital platforms and women-led majelis illustrates its adaptability to contemporary demands. The Haddadiyah model promotes values such as love, sincerity, humility, and social empathy, positioning Sufism not merely as a mystical path but as a transformative force in shaping moderate Islamic civilization. Keywords: Ba‘Alawi, dhikr, Hadramaut, moderation, Sufism Abstrak Artikel ini menelaah perkembangan Tarekat Hadadiyah di Indonesia pada abad ke-20 dengan menitikberatkan pada transmisi intelektual, jaringan spiritual, serta proses adaptasinya terhadap konteks lokal. Bersumber dari ajaran Imam al-Habib Abdullah bin Alawi al-Haddad di Hadramaut, Hadadiyah mencerminkan model tasawuf amali yang memadukan ritual dzikir, etika spiritual, dan keterlibatan keagamaan yang inklusif. Melalui pendekatan kualitatif berbasis studi pustaka dan analisis historis-konseptual, penelitian ini mengungkap bahwa penyebaran Hadadiyah berlangsung melalui struktur keagamaan nonformal dan peran aktif ulama dari jaringan Ba‘Alawi. Temuan menunjukkan bahwa tarekat ini berhasil berakulturasi dengan budaya lokal tanpa kehilangan keotentikan ajaran. Selain itu, pemanfaatan media digital serta partisipasi perempuan dalam majelis taklim memperlihatkan daya adaptif Hadadiyah terhadap zaman modern. Nilai-nilai seperti cinta, kejujuran, tawadhu‘, dan kepedulian sosial menjadi inti ajaran, menjadikan tasawuf Hadadiyah tidak hanya sebagai jalan spiritual personal, tetapi juga sebagai kekuatan transformasi peradaban Islam moderat yang inklusif.